Analisis perhitungan dan pelaporan Pajak Penghasilan Pasal 22 atas pengadaan barang pada Dinas Pendidikan Daerah Provinsi Sulawesi Utara berdasarkan PMK Nomor 59/PMK.03/2022 - Pailaha, Marcelio; Karamoy , Herman; Lambey, Robert (Riset Akuntansi dan Portofolio Investasi, 2024)
The North Sulawesi Province Regional Education Service is one of the government institutions that plays an important role in the collection of taxes on behalf of the government. In the current year, this third party is required to withhold, deposit, and report the tax owed on a monthly basis or during the relevant tax period. This research was conducted with the aim of determining the calculation and reporting of Income Tax Article 22 at the Regional Education Office of North Sulawesi Province, based on PMK Number 59/PMK.03/2022. This research employs a qualitative descriptive analytical method based on the results of interviews with several research informants. The findings indicate that the North Sulawesi Province Regional Education Service adheres to the applicable regulations in calculating Income Tax Article 22. However, there are discrepancies in the reporting process, whereby the reporting is submitted to BKAD (Regional Financial and Asset Agency) and not directly to KPP Pratama.